Mechanical Characteristics Of Oil Palm Fiber Reinforced Thermoplastics As Filament For Fused Deposition Modeling (FDM) - Ahmad, Mohd Nazri; Wahid, Mohammad Khalid; Maidin, Nurul Ain; Ab Rahman, Mohd Hidayat; Osman, Mohd Hairizal; Alis@Elias, Izzati Fatin (Springer, 2020)
Fibers are increasingly in demand for a wide range of polymer composite materials. This study’s purpose was the development of oil palm fiber (OPF) mixed with the thermoplastic material acrylonitrile butadiene styrene (ABS) as a composite filament for fused deposition modeling (FDM). The mechanical properties of this composite filament were then analyzed. OPF is a fiber extracted from empty fruit bunches, which has proved to be an excellent raw material for biocomposites. The cellulose content of OPF is 43%–65%, and the lignin content is 13%–25%. The composite filament consists of OPF (5%, mass fraction) in the ABS matrix. The fabrication procedure included alkalinizing, drying, and crushing the OPF to develop the composite. The OPF/ABS materials were prepared and completely blended to acquire a mix of 250 g of the material for the composition. Next, the FLD25 filament extrusion machine was used to form the OPF/ABS composite into a wire. This composite filament then was used in an FDM-based 3D printer to print the specimens. Finally, the printed specimens were tested for mechanical properties such as tensile and flexural strength. The results show that the presence of OPF had increased the tensile strength and modulus elasticity by approximately 1.9% and 1.05%, respectively. However, the flexural strength of the OPF/ABS composite had decreased by 90.6% compared with the virgin ABS. Lastly, the most significant outcome of the OPF/ABS composite was its suitability for printing using the FDM method.